The Pro-collusive Effect of Increased Cartel Detection Probabilities - Jeroen Hinloopen (Tinbergen Institute, 2004)
An increase in cartel discovery probability due to irregular price movements that result from cartel defection is shown to increase cartel stability as short-run defection profits are less likely to be earned.
Keywords: L12; L41; 330; cartel stability; detection probabilities; defection incentives; Kartell; Wettbewerbsbeschränkung; Wettbewerbsaufsicht; Theorie